Business Ecosystem Architecture Development: A Case Study of IoT Business in the Transportation Industry - Putra, Rahmat Hardian; Sutjipto, Mohammad Riza; Widodo, Aji; Kuntadi, Sri (Journal of Asian Multicultural Research for Economy and Management Study, 2024)
The research aims to study business ecosystem architecture in the Internet of Things (IoT) scope, especially in the transport industry. This research uses a qualitative approach with the Research and Development (R&D) method with the Modeling Business Ecosystem Architecture (TEAM) research design. Informants consist of internal and external sources who provide a practical and comprehensive perspective on the IoT transportation business ecosystem at Telkom Indonesia. Data collection was conducted through in-depth interviews, observations, and literature studies. The results showed that, in mapping the IoT business ecosystem in Telkom Indonesia’s transportation sector. The findings highlighted several challenges, such as the limited readiness of human resources and the lack of local device manufacturers resulting in a lack of competitiveness of IoT solutions. There is a need for a business ecosystem architecture that focuses on examining actors, roles, and value offered and mapping interactions between actors. With a cocreation approach, actors in the ecosystem can actively collaborate in designing, developing, and implementing more innovative and adaptive solutions. Through the cocreation process, customers, service providers, application developers, and other actors can share knowledge, experiences, and resources to create solutions that better suit the needs and expectations of all parties involved. This research maps the IoT business ecosystem in the transport sector developed by Telkom Indonesia. Telkom Indonesia is a solution provider, where the importance of collaboration of each actor, including device providers, application developers, and customers, is crucial to overcoming challenges and maximizing the ecosystem’s potential.